Functional Analysis Helps to Define KCNC3 Mutational Spectrum in Dutch Ataxia Cases - Duarri, Anna; Nibbeling, Esther A. R.; Fokkens, Michiel R.; Meijer, Michel; Boerrigter, Melissa; Verschuuren-Bemelmans, Corien C.; Kremer, Berry P. H.; van de Warrenburg, Bart P.; Dooijes, Dennis; Boddeke, Erik; Sinke, Richard J.; Verbeek, Dineke S. (PLOS ONE, 2015)
Spinocerebellar ataxia type 13 (SCA13) is an autosomal dominantly inherited neurodegenerative disorder of the cerebellum caused by mutations in the voltage gated potassium channel KCNC3. To identify novel pathogenic SCA13 mutations in KCNC3 and to gain insights into the disease prevalence in the Netherlands, we sequenced the entire coding region of KCNC3 in 848 Dutch cerebellar ataxia patients with familial or sporadic origin. We evaluated the pathogenicity of the identified variants by co-segregation analysis and in silico prediction followed by biochemical and electrophysiological studies. We identified 19 variants in KCNC3 including 2 non-coding, 11 missense and 6 synonymous variants. Two missense variants did not co-segregate with the disease and were excluded as potentially disease-causing mutations. We also identified the previously reported p.R420H and p.R423H mutations in our cohort. Of the remaining 7 missense variants, functional analysis revealed that 2 missense variants shifted Kv3.3 channel activation to more negative voltages. These variations were associated with early disease onset and mild intellectual disability. Additionally, one other missense variant shifted channel activation to more positive voltages and was associated with spastic ataxic gait. Whereas, the remaining missense variants did not change any of the channel characteristics. Of these three functional variants, only one variant was in silico predicted to be damaging and segregated with disease. The other two variants were in silico predicted to be benign and co-segregation analysis was not optimal or could only be partially confirmed. Therefore, we conclude that we have identified at least one novel pathogenic mutation in KCNC3 that cause SCA13 and two additionally potential SCA13 mutations. This leads to an estimate of SCA13 prevalence in the Netherlands to be between 0.6% and 1.3%.